2015
DOI: 10.1111/nph.13593
|View full text |Cite
|
Sign up to set email alerts
|

Model–data synthesis for the next generation of forest free‐air CO2 enrichment (FACE) experiments

Abstract: SummaryThe first generation of forest free-air CO 2 enrichment (FACE) experiments has successfully provided deeper understanding about how forests respond to an increasing CO 2 concentration in the atmosphere. Located in aggrading stands in the temperate zone, they have provided a strong foundation for testing critical assumptions in terrestrial biosphere models that are being used to project future interactions between forest productivity and the atmosphere, despite the limited inference space of these experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
210
1
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 207 publications
(217 citation statements)
references
References 95 publications
3
210
1
3
Order By: Relevance
“…Factors explaining this behavior are still not clear, but the main hypothesis is that the increase in forest productivity in recent years due to CO 2 fertilization effect could have accelerated the life cycle of trees, anticipating their death when still young (131,(139)(140)(141)(142). To reduce the uncertainties about the effect of increasing atmospheric CO 2 concentrations on tropical ecosystems, a group of international scientists are proposing to carry out a Forest Free-Air CO 2 Enrichment-type experiment in the Amazon (143).…”
Section: Impacts Of Anthropogenic Drivers Of Change In the Amazonmentioning
confidence: 99%
“…Factors explaining this behavior are still not clear, but the main hypothesis is that the increase in forest productivity in recent years due to CO 2 fertilization effect could have accelerated the life cycle of trees, anticipating their death when still young (131,(139)(140)(141)(142). To reduce the uncertainties about the effect of increasing atmospheric CO 2 concentrations on tropical ecosystems, a group of international scientists are proposing to carry out a Forest Free-Air CO 2 Enrichment-type experiment in the Amazon (143).…”
Section: Impacts Of Anthropogenic Drivers Of Change In the Amazonmentioning
confidence: 99%
“…In spring 2016, arable farmland areas were dosed repeatedly with soil fertilizer (ammomium nitrate and ammonium sulfate) with application rates of 45-80 kg N/ha, which are typical for these crop types in the UK [e.g., Outram et al, 2014]. Mean annual temperature at the site is 9°C, and mean annual precipitation is 690 mm [Norby et al, 2016]. Catchment geology is composed of red Permo-Triassic sandstone overlain by superficial deposits of glacial till up to 10 m thick, with organic-rich, sandy clay topsoils between 0.15 and 0.6 m thick.…”
Section: Site Descriptionmentioning
confidence: 99%
“…These studies have shown some consistent responses indicative of enhanced growth (Norby et al, 2016), as well as other physiological, morphological and ecosystem consequences, but also suffer from several structural deficiencies. Perhaps most notably, only short-term study periods are feasible; the longestrunning experiment spanned only a decade, while atmospheric CO2 has been steadily rising 20 for more than an order of magnitude longer than that duration.…”
Section: Introductionmentioning
confidence: 99%
“…Much debate, however, has centred on the drivers of this uptake. Suggested mechanisms include nitrogen deposition (Peterson and 5 Melillo, 1985), land use (Schimel, 1995), and the direct effects of carbon dioxide on plant growth (Norby et al, 2016). The last, which proposes that increased atmospheric CO2 yields increased photosynthetic rates, is both the most probable and the most controversial.…”
Section: Introductionmentioning
confidence: 99%